Beretning om agrikulturkemisk Virksomhed. Generalforsamling d. 15. december 1899. - Stein, V. (Tidsskrift for Landøkonomi, 2018)
Beretning om agrikulturkemisk Virksomhed. Generalforsamling d. 15. december 1899.